2021
DOI: 10.1093/mtomcs/mfab029
|View full text |Cite
|
Sign up to set email alerts
|

Pt-ttpy, a G-quadruplex binding platinum complex, induces telomere dysfunction and G-rich regions DNA damage

Abstract: Pt-ttpy (tolyl terpyridin-Pt complex) covalently binds to G-quadruplex (G4) structures in vitro and to telomeres in cellulo via its Pt moiety. Here, we identified its targets in the human genome, in comparison to Pt-tpy, its derivative without G4 affinity, and cisplatin. Pt-ttpy, but not Pt-tpy, induces the release of the shelterin protein TRF2 from telomeres concomitantly to the formation of DNA damage foci at telomeres but also at other chromosomal locations. γ-H2AX chromatin immunoprecipitation (ChIP-seq) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 95 publications
2
12
0
Order By: Relevance
“…With this in mind, we have performed γ-H2AX foci immunofluorescence (IF) analysis assays on A2780 cells treated for 4 days with the mono- and bimetallic NHC-Pt complexes, as well as with cisplatin, at their respective IC 80 concentrations for 4 days. Consistent with previous findings, , cisplatin induced significant accumulation of γ-H2AX foci. γ-H2AX foci were also detected in cells treated with the bimetallic NHC-Pt complexes D1–D4 and the mono-metallic complex M2, but not with M1 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, we have performed γ-H2AX foci immunofluorescence (IF) analysis assays on A2780 cells treated for 4 days with the mono- and bimetallic NHC-Pt complexes, as well as with cisplatin, at their respective IC 80 concentrations for 4 days. Consistent with previous findings, , cisplatin induced significant accumulation of γ-H2AX foci. γ-H2AX foci were also detected in cells treated with the bimetallic NHC-Pt complexes D1–D4 and the mono-metallic complex M2, but not with M1 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The platinum cellular uptake was quantified by ICP-MS (inductively coupled plasma mass spectrometry, NexION 2000, Perkin Elmer) on cellular pellets (5 × 10 6 cells) and DNA extracts (using DNeasy kit from Qiagen) as previously described. 44 A2780 and H1299 cells were treated with 1.5 μM M1, M2, D2, or D4 for 96 h. Trypan blue assay using the LUNA-II Automated Cell Counter showed that more than 96% of cells post NHC-Pt complexes' treatments remain viable. Around 20 μg of DNA (quantified by nanodrop) was extracted from pellets using the DNeasy Blood & Tissue Kit from Qiagen.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Moreover, the fluorescence intensity changes of CV2 in response to the addition of well‐known G4‐specific ligands (PhenDC 3 [37] and Pt‐ttpy [66] ) were examined in live HeLa cells. The intracellular green channel fluorescence of CV2 were reduced by ≈60 % upon pre‐incubation of PhenDC 3 (5 μM, 30 min) or Pt‐ttpy (2 μM, 24 h), while its red channel fluorescence intensities were not affected (Figures 7c–7d and S73).…”
Section: Resultsmentioning
confidence: 99%
“…The platinum cellular uptake was quantified by ICP-MS (Inductively Coupled Plasma Mass Spectrometry, Nex-ION ® 2000, Perkin Elmer, Courtaboeuf, France) on cellular pellets (5 × 10 6 cells), DNA extracts as previously described [27], and on isolated mitochondria. A2780 cells were treated with the IC 80 concentration of cisplatin, Pttppy and Pt-tpy for 96 h. DNA (quantified by nanodrop) was extracted from cell pellets using the DNeasy Blood & Tissue Kit (Qiagen) and mitochondria were isolated using the Mitochondria Isolation Kit for Cultured cell pellets (2 × 10 7 cells) (Thermo Scientific).…”
Section: Platinum Measurementmentioning
confidence: 99%
“…This compound is also able to efficiently trap G4s covalently by direct coordination to loop bases [23,24]. Our previous cellular and molecular mechanism studies indicate that Pt-ttpy binds covalently to telomeric DNA in cellulo [25], inducing chromosome loss and ultrafine bridges formation, resulting in telomeric DNA damage and telomere deprotection [26,27], by inducing DNA damage preferentially at Gand A-rich regions, displaying potent anti-tumor activity.…”
Section: Introductionmentioning
confidence: 97%